Dynamic of Thought on Asbābun Nuzūl : A Comparative Study by Andrew Rippin, Muhammad Syahrur and Roem Rowi - Muhammad Khoirul Rizal Affandi; Tesa Maulana (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This comparative study is motivated by the shift in the significance of Asbābun Nuzūl from a classical instrument to an object of epistemological debate. This research employs a library research method with an interpretive approach. Primary data sources consist of the works of Andrew Rippin, Muhammad Syahrur, and Roem Rowi, while secondary data sources include Qur'anic studies books and relevant journal articles. Data were collected through documentation and analyzed using comparative techniques. The findings reveal that Rippin presents a critical and skeptical perspective regarding the authenticity of Asbābun Nuzūl narratives. Syahrur emphasizes the socio-historical context and limits the relevance of Asbābun Nuzūl . Roem Rowi offers a balanced approach by integrating historical, linguistic, and thematic dimensions.